2016
DOI: 10.1007/978-1-4939-6637-0_20
|View full text |Cite
|
Sign up to set email alerts
|

EpiSweep: Computationally Driven Reengineering of Therapeutic Proteins to Reduce Immunogenicity While Maintaining Function

Abstract: Therapeutic proteins are yielding ever more advanced and efficacious new drugs, but the biological origins of these highly effective therapeutics renders them subject to immune surveillance within the patient’s body. When recognized by the immune system as a foreign agent, protein drugs elicit a coordinated response that can manifest a range of clinical complications including rapid drug clearance, loss of functionality and efficacy, delayed infusion-like allergic reactions, more serious anaphylactic shock, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Ab–Ag docking models were generated by the ClusPro server ( Brenke et al, 2012 ; Comeau et al, 2004a ), which in a recent Ab–Ag docking benchmark ( Brenke et al, 2012 ) demonstrated a near-native docking model among its top 30 predictions in 95% of test cases. For each model, site-directed mutagenesis based Ag variants were computationally designed ( Choi et al, 2017 ; Parker et al, 2013 ) to disrupt Ab binding, as evaluated by a sequence potential ( Pons et al, 2011 ), while maintaining Ag stability, as evaluated by molecular mechanics modeling ( Gainza et al, 2013 ; Pearlman et al, 1995 ). These two properties were balanced in a Pareto optimal fashion ( He et al, 2015 ), with the goal of ensuring that variants still express and fold similarly to the wild type protein, thereby enabling confident interpretation of Ab binding results.…”
Section: Resultsmentioning
confidence: 99%
“…Ab–Ag docking models were generated by the ClusPro server ( Brenke et al, 2012 ; Comeau et al, 2004a ), which in a recent Ab–Ag docking benchmark ( Brenke et al, 2012 ) demonstrated a near-native docking model among its top 30 predictions in 95% of test cases. For each model, site-directed mutagenesis based Ag variants were computationally designed ( Choi et al, 2017 ; Parker et al, 2013 ) to disrupt Ab binding, as evaluated by a sequence potential ( Pons et al, 2011 ), while maintaining Ag stability, as evaluated by molecular mechanics modeling ( Gainza et al, 2013 ; Pearlman et al, 1995 ). These two properties were balanced in a Pareto optimal fashion ( He et al, 2015 ), with the goal of ensuring that variants still express and fold similarly to the wild type protein, thereby enabling confident interpretation of Ab binding results.…”
Section: Resultsmentioning
confidence: 99%
“…[231][232][233][234][235] The integrated methods developed by Bailey-Kellogg, Griswold, and coworkers are available upon request through the corresponding authors as the EpiSweep package. 199…”
Section: Antibody Humanizationmentioning
confidence: 99%
“…Previous studies have reported different strategies to generate amino acid substitutions for the purpose of reducing immunogenicity (for recent studies see refs ). In several studies, alanine replacements have been used (see refs ).…”
Section: Resultsmentioning
confidence: 99%
“…Other de‐immunization studies also based on introducing single amino acid substitutions into known epitopes have been reported in the literature (see, for example, refs , as cited above). In those studies, mild and conservative substitution strategies, such as ‘alanine scans’, were shown to be effective.…”
Section: Discussionmentioning
confidence: 99%